Factors Associated with Non-Enrollment in National Health Insurance Scheme in Kaski District, Nepal - Adhikari, Anju; Gahatraj, Nand Ram; Yadav, Dipendra Kumar (Nepalese Journal of Insurance and Social Security, 2020)
Health insurance poses a vital role in developing countries, to attain an equitable health outcome to all citizens by ensuring universal health coverage.  This study aims to assess the factors associated with non-enrollment in National Health Insurance Scheme (NHIS) in a setting of Nepal. A cross-sectional study was conducted among 492 households (246 non-enrolled and 246 enrolled) of Kaski district, Nepal from May to August 2020. Data were gathered from face-to-face interview. Data were entered in Epi data 3.1 and analysed by using statistical package for social sciences (SPSS16).  Descriptive and inferential statistics were performed to analyze the data. The household without elderly family members were 2.06 times less likely to enroll in the scheme (AOR=2.060, CI=1.141-3.721, p